Nudge on Choice Architecture: Effectiveness of Economic Recovery Policy and Irrational Behavior Predictions - Rahmawati, Titi (Research and Development Agency Ministry of Home Affairs, 2022)
Economic recovery policy in low-income communities is a priority of the government in tackling the tidal wave of the economy during the COVID-19 pandemic. This study aims to map the government's priorities and rapid action in its careful planning also implementation. The challenge is how society has a drive about a wide range of choices that have many possibilities, namely maximizing added value to the aid or fulfilling desires that approach irrational behavior. Therefore, encouragement is needed by every individual to choose choices that are in line with the government's policy objectives to eliminate or eliminate extreme poverty. The method used is an analysis of social science and behavioral science with circumplex strategy, which is further analyzed in correlation with quantitative methods using Kendall W. Test analysis and continued double regression. The results showed that encouragement had a positive and insignificant influence on the effectiveness of BLT policies; predictions of irrational behavior have a negative and insignificant influence on the effectiveness of BLT policies; And together, nudge and irrational predictably have a positive and significant influence on the effectiveness of Top Up BLT policies. Recommendations on the encouragement in improving the architecture of choice are the collaboration between the program implementation team and related stakeholders; irrational behavior predictions are anticipating irrational behavior tendencies by understanding the vulnerability of preconditions and conditions in the implementation of the program; the maintenance of the commitment of the central and local government and village government in enforcing regulations.